The Management of Sundanese Cultural Local Wisdom Learning in developing Early Childhood Nationalist Character - Ricky Yoseptry (AL-ISHLAH: Jurnal Pendidikan, 2022)
The background of this research is that education functions to empower human potential to inherit, shape, and build future culture and civilization.  This study aimed to obtain an overview and information about learning Sundanese local wisdom in shaping the nationalist character in early childhood. This research was conducted in Puji Handayani Kindergarten, Cimahi CIty. This study uses a qualitative approach with a case study method, where the researcher observes directly how Sundanese local wisdom learning activities are carried out in Puji Handayani Kindergarten. This study concludes that Puji Handayani Kindergarten organizes learning of Sundanese local wisdom in shaping nationalist character in early childhood with the proper steps. Planning is prepared carefully since the beginning of the school year together with all components of the institution, which is poured in writing into the Semester Plan. The implementation of learning local wisdom of Sundanese culture in forming nationalist character in early childhood is carried out through four stages; namely, the planting, growing, carrying out, and stabilizing stages which are realized from the beginning of entry until it is time to go home including opening, core, resting/eating activities, and closing activities. From the management of the school, it has an impact on the formation of the child's nationalist character. The solution to overcome the obstacles in implementing Sundanese cultural local wisdom learning in forming a nationalist character in early childhood is to involve teachers in several pieces of training for learning Sundanese local wisdom and to explore various games of Sundanese local wisdom.